Where AD plants wildly grow: The spatio-temporal diffusion of agricultural biogas production in the Czech Republic. (September 2016) - Martinát, Stanislav; Navrátil, Josef; Dvořák, Petr; Van der Horst, Dan; Klusáček, Petr; Kunc, Josef; Frantál, Bohumil
Abstract: There is fundamental agreement about the environmental benefits of renewable energy technologies, but unintended consequences arising from their deployment are frequent sources of conflicts. The Czech Republic has committed itself to supply 13.5% of its electricity consumption from renewable sources by 2020. High state incentives for renewable energies have been provided to achieve this target, however critical questions can be asked about the appropriateness of the design of the supporting frameworks which caused a boom in photo-voltaic (PV) installations on agricultural land, as well as a boom in the installation of agricultural anaerobic digestion (AD) plants fuelled by dedicated energy crops. This paper analyses the diffusion of agricultural AD plants in the Czech Republic, focusing especially on locational characteristics in relation to the quality of agricultural land, agricultural and population census data. Statistical analysis of those spatial datasets show that agricultural AD plants are mostly located in less favourable agricultural areas, in regions having recently experienced a reduction in cattle breeding, and in regions with significant increases of sowing areas of green maize. These findings suggests shortcomings in the supporting policy for AD plants in the Czech Republic, resulting in unintended environmental consequences, and missed opportunities to enhance energy self-sufficiency and resilience in the countryside. Highlights: The boom in anaerobic digestion plants in the Czech Republic is spatially evaluated. Spatial coherences of natural, agricultural, and socioeconomic conditions are assessed. Anaerobic digestion plants are mainly located in under-average natural conditions. Plants are mainly fed by green maize and fodder crops instead of agricultural waste. Misguided supporting policy results in unintended environmental consequences.